Plate Augmentation in Aseptic Femoral Shaft Nonunion after Intramedullary Nailing: A Literature Review - Carlo Perisano; Luigi Cianni; Chiara Polichetti; Adriano Cannella; Massimiliano Mosca; Silvio Caravelli; Giulio Maccauro; Tommaso Greco (Bioengineering, 2022)
Background: Femoral shaft fractures (FSFs) are a frequent injury in traumatology for which intramedullary nailing (IMN) is considered the gold standard treatment. Nonunion (NU) is one of the most frequent complications in FSF treated with IMN, with a percentage from 1.1% to 14%. Plate augmentation (PA), the addition of a compression plate and screws, with or without bone graft has been described as an effective option for the treatment of NU, improving the biomechanical conditions at the fracture site. The aim of this review was to analyze the literature relating to the use of PA in NU after IMN in FSFs to assess the efficacy of the technique. Methods: An electronic search on PubMed, Google Scholar, and Web of Science was conducted to search for all studies concerning PA of femoral shaft NUs after IMN. Results: Twenty-four studies were included in the review comprising a total of 502 patients with a mean age of 39.5 years. Of these, 200 hundred patients had atrophic pseudoarthrosis and 123 had hypertrophic pseudoarthrosis, while in 179, the type of pseudoarthrosis was not reported. The most frequently used plate for PA was the dynamic compression plate (DCP); in 87.1% of the cases, the authors added a bone graft to the plate fixation. In 98.0% of the patients, a complete bone union was achieved in a mean time of 5.8 ± 2.12 months. Conclusion: The patients treated with PA included in this review showed a good rate of consolidation in the femoral shaft NUs, with good functional recovery and a low incidence of complications.